2014
DOI: 10.1080/15546128.2014.903815
|View full text |Cite|
|
Sign up to set email alerts
|

Adult Role Models: Feasibility, Acceptability, and Initial Outcomes for Sex Education

Abstract: We present the feasibility and acceptability of a parent sexuality education program led by peer educators in community settings. We also report the results of an outcome evaluation with 71 parents who were randomized to the intervention or a control group, and surveyed one month prior to and six months after the 4-week intervention. The program was highly feasible and acceptable to participants, and the curriculum was implemented with a high level of fidelity and facilitator quality. Pilot data show promising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…The role of parents does not directly affect reproductive health behavior. Basically, the fundamentals of reproductive health education are arranged from childhood and through family contributions (19). The results of this study are consistent with findings from a systematic study of studies conducted in Indonesia (20).…”
Section: Literature Reviewsupporting
confidence: 89%
“…The role of parents does not directly affect reproductive health behavior. Basically, the fundamentals of reproductive health education are arranged from childhood and through family contributions (19). The results of this study are consistent with findings from a systematic study of studies conducted in Indonesia (20).…”
Section: Literature Reviewsupporting
confidence: 89%
“…After a content analysis of the various educational interventions, it was ascertained that the majority (n= 17), used active teaching-learning methods and belonged to the integrative model (Adams et al, 1990;Baldissera et al, 2012;Ballester-Arnal et al, 2016;Bauer et al, 2013;DiGioia, 2011;Feuz et al, 2019;Hernández Carrasco et al, 2019;Klein et al, 2005;Lee et al, 2020;Martin et al, 2018;Mayers & McBride, 1998;Nicols et al, 2007;O'Neil & Carroll, 1988;Opazo Pérez, 2018;Pastor et al, 1992;Risman, 2011;Vitória, 2019). A slightly lower number (n= 8) was consistent with the preventive model (Cardoso Junior, 2012;Colarossi et al, 2014;Gedin & Resnick, 2014;Goldberger, 2018;Goldman & Carroll, 1990;Jones & Moyle, 2016;Livni, 1994;Rodríguez Maresma, 2009) while none had the features of the moral model (n= 0). The issue of equality between men and women was only addressed in three interventions (Ballester-Arnal et al, 2016;O'Neil & Carroll, 1988;Pastor et al, 1992).…”
Section: Results / Findingsmentioning
confidence: 83%
“…Two studies by Colarossi et al 17 and Svanemyr et al 25 present strategies that focus on SRH role modelling. The strategies include a curriculum-based peer educator SRH role modelling programme, creating safe spaces for adolescent girls, parental engagement, mentoring, and positive role modelling, Mobilisation of adults and community leaders, working with boys, and encouraging men to promote gender-equitable norms.…”
Section: Resultsmentioning
confidence: 99%
“…Adolescents in the schoolbased programme were allowed to improve their SRH by learning about SRH decision-making, self-care, and being responsible in sexual and emotional relationships. 33 A study by Colarossi et al 17 reported on an adult program for role models for adolescents' SRH. The curriculumbased programme is a 4-week workshop led by parent-peer educators in the community.…”
Section: Theme 3: Mentoring and Positive Role Modellingmentioning
confidence: 99%
See 1 more Smart Citation